Dutch-Indonesian interlanguage; Psycholinguistic study on syntax - Riyanto, Sugeng (Wacana, Journal of the Humanities of Indonesia, 2012)
This article focuses on the psycholinguistic study of the syntactic aspects of Dutch-Indonesian interlanguage. The study is based on the interlanguage syntax observed in an oral test given to thirty Indonesian learners of Dutch as a second language, whose purpose is to test the processability theory of Pienemann (2005a, b, c, 2007). The results of the study provide evidence for the validity of Pienemann's theory. Learners who have acquired sentences with the highest level of processing will also already have acquired sentences with a lower level of processing. The results from learners with a high level of Dutch proficiency verify the processability theory with more certainty than the results of learners with a lower proficiency. Learners tend to rely on meaning if they are not confident of their grammatical proficiency. Interlanguage is the result of the immediate need to encode in the mind concepts and ideas into the form of linguistic items, within a fraction of a millisecond, whilst the supporting means are limited, and whilst learners already have acquired a first language and possibly another language as well.